2007
DOI: 10.1016/j.bbamcr.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

MAD2 expression and its significance in mitotic checkpoint control in testicular germ cell tumour

Abstract: Chromosomal instability (CIN) is a common characteristic in testicular germ cell tumour (TGCT). A functional mitotic checkpoint control is important for accurate chromosome segregation during mitosis. Mitotic arrest deficient 2 (MAD2) is a key component of this checkpoint and inactivation of MAD2 is correlated with checkpoint impairment. The aim of this study was to investigate the function of mitotic checkpoint control in TGCT cells and to study its association with MAD2 expression using 8 TGCT cell lines as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…In summary, we have shown that down-regulation of MAD2, a feature common to many tumour cell lineages (Takahashi et al, 1999;Wang et al, 2000Wang et al, , 2002Fung et al, 2007) induces cellular senescence in up to a third of the cell population. Due to the fact that paclitaxel targets actively dividing cells, these cells will evade cytotoxic-induced death.…”
Section: Discussionmentioning
confidence: 54%
“…In summary, we have shown that down-regulation of MAD2, a feature common to many tumour cell lineages (Takahashi et al, 1999;Wang et al, 2000Wang et al, , 2002Fung et al, 2007) induces cellular senescence in up to a third of the cell population. Due to the fact that paclitaxel targets actively dividing cells, these cells will evade cytotoxic-induced death.…”
Section: Discussionmentioning
confidence: 54%
“…7,8,15 To confirm the involvement of MTBP in the mitotic checkpoint, we examined the percentage of mitotic cells (mitotic index) following treatment of cells with nocodazole or dimethyl sulfoxide (DMSO; Figure 3c). We measured the mitotic index via flow cytometry using a histone H3 S10P antibody in combination with DNA content analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of MAD 2 gene expression leads to defects in the mitotic checkpoint, chromosome mis-segregation, and tumorigenesis [6, 10]. In human cancer, there have been only a few reports regarding altered MAD 2 gene expression [10,29,30,31,32,33]. MAD 2 gene is up- or downregulated depending on the tumor type, and both alterations seem to be involved in tumor development.…”
Section: Discussionmentioning
confidence: 99%